(untitled) (Raparin Journal of Humanities (RJH), 2026)
This paper discusses the geopolitical rivalries between the United States and Iran, the United States as a global power and Iran as a regional power, in the context of security dynamics in the Kurdistan Region of Iraq (KRI) using the Regional Security Complex Theory (RSCT) as a tool of analysis. Although constitutionally recognized, The KRI exists as a non-state actor in a contested sphere of influence within the broader Middle Eastern Security Complex. Using a qualitative methodology and discourse analysis of political statements and events, the paper explores the effects of the American military presence and Iranian proxy activities on the domestic security of the KRI. These findings reveal that the United States has been selectively offering military assistance without politically supporting Kurdish aspirations for independence, while Iran has been putting more pressure through its proxy militia groups, missile strikes and economic pressures. These tensions were further intensified by the 2020 assassination of Qassem Soleimani, which significantly rendering the region’s vulnerability to proxy related violence. RSCT offers a critical framework for understanding the sub-state vulnerabilities in complex regional conflicts and reveals how the security of the KRI is fundamentally intertwined with the dynamics of regional power politics. Moreover, the research provides to both theoretical and practical literature about the way in which regional conflicts undermine constitutionally autonomous actors like the KRI. Eventually, the paper demonstrates that the security situation in the KRI is shaped by its entrenchment in the broader geopolitical rivalries between global and regional powers.